KORELASI KEMATANGAN EMOSI DENGAN PENGAMBILAN KEPUTUSAN KARIER PADA SISWA KELAS XII MAN 1 JEMBER - Nailatul Husna; As’ad; Moh. Hafid (Konseling At-Tawazun, 2024)
Career decision making is a thinking process in selecting and determining various existing career options. This research aims to determine the relationship between emotional maturity and career decision making in class XII students at MAN 1 Jember. This research is quantitative research with a correlation type of research. Based on the research results, there is a weak relationship between emotional maturity and career decision making in class XII students at MAN 1 Jember with a positive direction. This is proven by using the Product Moment correlation test with a sig=765 value of more than 0.05. And a value of 0.30 indicates a low correlation coefficient because it is in the range of 0.25-0.40. So, the higher the emotional maturity of class XII MAN 1 Jember students, the higher the career decision making of class XII MAN 1 Jember students.